Allelic, Genotypic and Phenotypic Frequency Of Abo and Rhesus (D) Blood Groups in Noakhali, Feni and Sherpur Districts of Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2017)
Background: Genetic characteristics (allelic and genotypic frequencies; phenotypic distribution) of ABO and rhesus (D) blood group systems of Bengali population from Feni, Noakhali and Sherpur districts are unknown. This has stimulated us to conduct the study. Materials and methods: A retrospective study (2013-2015) was done from blood group data obtained from the registers of the blood banks in district hospitals of Feni, Noakhali and Sherpur. Hardy- Weinberg formula was used to determine allele and genotype distribution. Results: Total subjects from the three centers were 8058. Observed allelic (O > B > A) and phenotypic frequency (O > B > A > AB) was similar in all centers. Allele frequency range was IA 0.1826 to 0.1946, IB 0.2082 to 0.2292 and IO 0.5768 to 0.6092. Rhesus (D) allele frequency was Id 0.1315 to 0.1615 and ID 0.8385 to 0.8685. Rhesus negative blood groups were scarce (%). Conclusion: Genetic characteristics of ABO and rhesus blood group genes of studied population are in agreement with the existing data about Bangladeshi population.JCMCTA 2017 ; 28 (1) : 38 - 41